Hygro-thermal vibration behavior of porous functionally graded nanobeams based on doublet mechanics (Archives of Mechanics - Test, 2024)
This study deals with the vibration response of porous functionally graded (FG) nanobeams under hygro-thermal loadings. The FG nanobeam model is developed based on the Euler–Bernoulli beam theory, in which the doublet mechanics is implemented to account for the size effect. The material properties of the FG nanobeam are assumed to vary along the thickness direction of the beam according to the power-law form with the temperature dependent and porosity phases. The approximate Ritz method is employed to obtain the natural frequencies of porous FG nanobeam models for various boundary conditions. The influences of several parameters such as temperature rise, moisture concentration, porosity volume fraction, material gradient index, material length scale parameter and mode number on the free vibration response of the porous FG nanobeams under hygro-thermal environments are examined in detail. It is explicitly shown that the proposed approach can provide accurate frequency results of FG nanobeams as compared to existing studies in open literature. These study’s results may be useful for the optimal and safety design of nano-electro-mechanical systems.